2021
DOI: 10.1186/s12889-021-11198-6
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage estimates and utilization patterns of inactivated enterovirus 71 vaccine post vaccine introduction in Ningbo, China

Abstract: Background In China, enterovirus 71 (EV71) is the major etiological agents of hand foot mouth disease that poses severe risks to children’s health. Since 2015, three inactivated EV71 vaccines have been approved for use. Previous studies indicated the high willingness of EV71 vaccination in eastern China. However, few studies have assessed coverage and utilization patterns of EV71 vaccine in China. Methods Children born during 2012–2018 were sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We have shown high newborn-completion-vaccination rates (71.33% in 2018) in Hefei while Guangzhou had a 15.11% rate in 2018 [ 42 ]. In Ningbo, the newborn-completion-vaccination rate was 44.23% [ 43 ], and the incidence density was as high as 5 945.50/10 5 person-years [ 33 ]. Countries such as Japan and Singapore also have a high prevalence of HFMD, but did not use the EV-A71 vaccine, although EV-A71 prevalence dropped in 2015 but subsequently increased thereafter [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown high newborn-completion-vaccination rates (71.33% in 2018) in Hefei while Guangzhou had a 15.11% rate in 2018 [ 42 ]. In Ningbo, the newborn-completion-vaccination rate was 44.23% [ 43 ], and the incidence density was as high as 5 945.50/10 5 person-years [ 33 ]. Countries such as Japan and Singapore also have a high prevalence of HFMD, but did not use the EV-A71 vaccine, although EV-A71 prevalence dropped in 2015 but subsequently increased thereafter [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future attention should be focused to continuously improve maintenance of vaccination. Notably, the guidelines recommend completion of EV-A71 with two doses before 12 months of age suggesting timeliness was considered to be an indicator of the effectiveness of EV71 vaccine [ 43 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal age for EV-A71 vaccination is from 6 months to 71 months of age, and full vaccination is encouraged to be completed before the infant reaches 12 months of age ( 41 ). The current coverage of EV-A71 vaccine in China is not very high as the previous researches showed that the vaccination coverage rate in Guangdong Province was rose from 3.82 to 10.07% in 2016 and 2017 ( 42 ), and the EV71 vaccination rate in Ningbo City was 24.05% among 716,178 children born from 2012 to 2018, with a timely vaccination rate of only 8.61% ( 43 ). In Kunming, a central city in southwest China, about 19.16% of children were vaccinated in 2018.…”
Section: Discussionmentioning
confidence: 98%
“…In 2018, the incidence in Zhejiang and Jiangsu reached the highest value after the vaccine was launched, which was 436.02 per 100,000 in Zhejiang and 237.50 per 100,000 in Jiangsu, and Zhejiang had the highest incidence in the country. EV-A71 vaccine coverage rate had increased year by year to 24.05% in Zhejiang, higher than 19.4% in Guangdong [ 77 ]. The proportion of EV-A71 positive cases declined from 22.6% in 2017 to 3.3% in 2018 in Zhejiang [ 78 ].…”
Section: Discussionmentioning
confidence: 99%